Semi-commercial use of chlorramine-T as an effective treatment of AGD in farmed Tasmanian Atlantic salmon, Salmo salar) L - Powell, MD; Harris, JO; Attard, M; Green, TJ; DeHayr, L; Roberts, SB (2003)
No description available